Inspiration (Ilhām) and Its Sharʿī Status in the Thought of Shaykh al-Akbar Ibn ʿArabī, as Presented in Al-Futūḥāt al-Makkiyya - Dr. Umair Mahmood Siddiqui; Dr. Muhammad Zahid Siddique (Journal of Religion and Society, 2025)
This paper explores the Sharʿī (legal-religious) standing of ilhām (divine inspiration) in the metaphysical system of Shaykh al-Akbar Muḥyī al-Dīn Ibn ʿArabī. Focusing on his authoritative work al-Futūḥāt al-Makkiyya, it establishes that Ibn ʿArabī viewed inspiration and unveiling (kashf) as valid epistemological tools for spiritual understanding, not as independent sources of law. The research clarifies the essential difference between waḥy (prophetic revelation) and ilhām, affirming that the latter does not carry legislative force and must never contradict the Qur'an, Sunnah, or the finality of Prophethood (khatm al-nubuwwah). The study directly addresses and refutes the major objections raised by his critics such as accusations of introducing new legislation or undermining the authority of revelation by presenting Ibn ʿArabī’s own detailed statements. It concludes that in Ibn ʿArabī’s view, inspiration is a personal, spiritually illuminating experience that assists in understanding divine law, but can never alter or replace it. Keywords: Ibn ʿArabī, Ilhām, Kashf, Waḥy, Islamic Law, Sufi Epistemology, Divine Inspiration, Revelation